Prognostic Value of Neoantigen Load in Immune Checkpoint Inhibitor Therapy for Cancer - Zou, Xue-lin; Li, Xiao-bo; Ke, Hua; Zhang, Guang-yan; Tang, Qing; Yuan, Jiao; Zhou, Chen-jiao; Zhang, Ji-liang; Zhang, Rui; Chen, Wei-yong (Frontiers in Immunology, 2021)
Immune checkpoint inhibitors (ICIs) have made great progress in the field of tumors and have become an important development direction of tumor treatment. With advancements in genomics and bioinformatics technology, it is possible to individually analyze neoantigens produced by somatic mutations of each patient. Neoantigen load (NAL), a promising biomarker for predicting the efficacy of ICIs, has been extensively studied. This article reviews the research progress on NAL as a biomarker for predicting the anti-tumor effects of ICI and provides a summary of the definition of NAL, detection methods, and their relationship with tumor mutation burden. In addition, we describe common genomic sources of NAL. Finally, we review the predictive value of NAL as a tumor prediction marker in various clinical studies. In this review, we focus on analyzing NAL’s prediction of the efficacy of ICIs for tumors. In melanoma, lung cancer, and gynecological tumors, NAL can be considered a predictor of treatment efficacy. In contrast, the use of NAL for urinary system and liver tumors requires further research. When NAL alone is insufficient to predict efficacy, its combination with other indicators can improve prediction efficiency. Evaluating the response of predictive biomarkers before the start of treatment is essential for guiding the clinical treatment of cancer. The predictive power of NAL has great potential; however, it needs to be based on more accurate sequencing platforms and technologies.